Becoming Spider-Man - Palacios, Tomas (World of reading (New York, N.Y.)., 2012)
"Peter Parker is a regular kid in high school. After a visit to Oscorp and an encounter with a strange spider, everything in Peter's life suddenly changes! He is now able to cling to ceilings, climb up walls, and eat everything in Aunt May's fridge. Realizing he has Super Powers and a responsibility to use them for good, Peter must save the day by becoming the Amazing Spider-Man!"--P. [4] of cover.